2012
DOI: 10.1186/1743-7075-9-107
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and adiponectin levels are associated with height catch-up growth in pre-pubertal Chinese individuals born small for gestational age

Abstract: AbstractsBackground and objectiveThe study was performed to determine whether catch-up growth is associated with the development of insulin resistance and to explore serum endocrine markers associated with the metabolism of adipose tissue in a Chinese population born small for gestational age(SGA)Subjects and methodsWe recruited 56 children born SGA with catch-up growth and 55 born without catch-up growth, who were further grouped into groups I (with BMI catch-up) and II (without BMI catch-up) respectively, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…However, Deng et al [14] found a higher concentration of insulin only in those SGA children with catch-up growth in whom BMI values were above the 50th percentile. In the whole study group, analysed by us, we also found a positive correlation between BMI SDS and insulin concentration (or IRI HOMA).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, Deng et al [14] found a higher concentration of insulin only in those SGA children with catch-up growth in whom BMI values were above the 50th percentile. In the whole study group, analysed by us, we also found a positive correlation between BMI SDS and insulin concentration (or IRI HOMA).…”
Section: Discussionmentioning
confidence: 96%
“…In turn, high resistin levels were found in cord blood of SGA children [9,12]. Low adiponectin with high insulin secretion in prepubertal children with catch-up process was observed by other authors [13][14][15]. It should be emphasised that hypoadiponectinaemia and hyperresistinaemia are strongly associated with an increased risk of IR, DM2 and cardiovascular diseases [16].…”
Section: Introductionmentioning
confidence: 86%
“…The upregulation of PI 3-kinase signalling was associated with increased activity of growth factor pathways (for example, IGF-I and EGF pathways) and the increase of serum IGF-I observed in CU SGA children (Figure 4). The observed downregulation of PI4PK3 in CU SGA children has been previously associated with a reduction in cell surface glucose receptors, 64 which may be related to the increased serum glucose in this group 52 (Table 1). We also predicted that the increased activity downstream of the PI pathways would be associated with an increase in calcium signalling, which is required for multiple cell functions including insulin secretion 65 (Figure 4).…”
Section: Discussionmentioning
confidence: 63%
“…Integrated omic analysis of SGA catch-up growth A Stevens et al but lower adiponectin levels, as recently described, and potentially consistent with an early indicator of cardiometabolic risk. 52,53 Adiponectin is a protein derived from the adipose tissue in humans and has been related to obesity and insulin resistance. 54 There is functional evidence that it has a protective role in the development of metabolic complications, as high concentrations have been associated with a reduced risk of type 2 diabetes, and low levels with the converse.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, higher levels of insulin concentration and IRI HOMA in SGA than AGA children are reported, especially in those of SGA in whom rapid weight gain in the first years of life was observed [37]. The authors suspected that it may be a risk factor for the development of IR and T2DM in later life.…”
Section: Discussionmentioning
confidence: 90%